Molecular dynamics simulation at the early stage of thin-film deposition: Al or Co on Co(111) - Kim, SP; Lee, SC; Lee, KR; Chung, YC (JAPAN SOC APPLIED PHYSICS, 2004)
The growth mechanisms at the early stage of thin-film deposition were quantitatively investigated using the molecular dynamics method, focusing on the cases of Al and Co on an fcc-Co(111) system. In the case of Al on Co(111), Al adatoms were grown basically in the layer-by-layer growth mode. Moreover, this growth behavior became more obvious with increasing substrate temperature from 80 K to 300 K. In the case of Co on Co(111), Co adatoms apparently favored the island growth mode at a low incident energy. By increasing the energy, however, the tendency towards the layer-by-layer growth mode highly increased. These could be explained by the difference in surface diffusion barrier between the two cases.
Keywords: TEMPERATURE EPITAXIAL-GROWTH; SURFACE